Adaptive capacity: proposition and validation of a measurement scale - Zaluski, Felipe Cavalheiro; Hedlund, Patrique Rosa; Cordeiro, Marcelo de Moraes; Sausen, Jorge Oneide (Revista de Administração da UFSM, 2022)
Purpose The paper aims to propose and validate a scale for measuring adaptive capacity in organizations. Design / methodology / approach To propose the scale dimensions, the model by Stabler and Sydow (2002) was taken into account and to propose the indicators for each dimension, previous studies related to the theme were analyzed based on a systematic review on academic bases. For quantitative validation of the scale, an e-survey was adopted in 122 organizations in the Northwest Colonial region of the State of Rio Grande do Sul, Brazil, using structural equation modeling (MEE) with the SmartPLS 3.2.8 software as support. Findings The results of the study demonstrate the articulation of the indicators of Flexible Organizational Structure and Innovative Management, Plurality and Multifunctionality of Teams and Information Systems and Market Analysis result in a scale in which several aspects related to the existence of the development of adaptive capacities in organizations can be analyzed. Research limitations / implications It is noteworthy that the sample considered for the analysis￼ is based on a specific region, therefore, its results should be interpreted with caution. Practical implications The scale contributes to instrumenting the managers allowing the identification of weaknesses, relevant to the dimensions and indicators, so that the managers can guide their efforts. Originality / value This study shows itself to be prominent, since its measurement and validation of a scale based on the development of adaptive capacity will allow, in such a way, other studies and also new comparisons for the advancement of the subject.